Analysis of a Predator-Prey Model with Distributed Delay. (3rd May 2021) - Chandrasekar, Gunasundari; Boulaaras, Salah Mahmoud; Murugaiah, Senthilkumaran; Gnanaprakasam, Arul Joseph; Cherif, Bahri Belkacem
Abstract : In this paper, we consider a predator-prey model, where we assumed that the model to be an infected predator-free equilibrium one. The model includes a distributed delay to describe the time between the predator's capture of the prey and its conversion to biomass for predators. When the delay is absent, the model exhibits asymptotic convergence to an equilibrium. Therefore, any nonequilibrium dynamics in the model when the delay is included can be attributed to the delay's inclusion. We assume that the delay is distributed and model the delay using integrodifferential equations. We established the well-posedness and basic properties of solutions of the model with nonspecified delay. Then, we analyzed the local and global dynamics as the mean delay varies.